2017
DOI: 10.1073/pnas.1616287114
|View full text |Cite
|
Sign up to set email alerts
|

High Arctic Holocene temperature record from the Agassiz ice cap and Greenland ice sheet evolution

Abstract: We present a revised and extended high Arctic air temperature reconstruction from a single proxy that spans the past ∼12,000 y (up to 2009 CE). Our reconstruction from the Agassiz ice cap (Ellesmere Island, Canada) indicates an earlier and warmer Holocene thermal maximum with early Holocene temperatures that are 4-5°C warmer compared with a previous reconstruction, and regularly exceed contemporary values for a period of ∼3,000 y. Our results show that air temperatures in this region are now at their warmest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
197
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(223 citation statements)
references
References 31 publications
26
197
0
Order By: Relevance
“…The GISP2 melt layers suggest a summer thermal maximum from roughly 9-6 ka BP, shorter in duration than, but overlapping in time with, the broad HTM that we find in Greenland SAT between 10 and 6 ka BP (Figure 2d). Recently, Lecavalier et al (2017) suggested that the timing of the HTM is earlier (11-10 ka BP) on Ellesmere Island, based on elevation-corrected records of summer melt and water isotopes-at that same location our merged product suggests maximum HTM warmth to occur around 9.5 ka BP (Figure 2h). Recently, Lecavalier et al (2017) suggested that the timing of the HTM is earlier (11-10 ka BP) on Ellesmere Island, based on elevation-corrected records of summer melt and water isotopes-at that same location our merged product suggests maximum HTM warmth to occur around 9.5 ka BP (Figure 2h).…”
Section: Evaluating the Gis Surface Temperature Fieldssupporting
confidence: 52%
See 1 more Smart Citation
“…The GISP2 melt layers suggest a summer thermal maximum from roughly 9-6 ka BP, shorter in duration than, but overlapping in time with, the broad HTM that we find in Greenland SAT between 10 and 6 ka BP (Figure 2d). Recently, Lecavalier et al (2017) suggested that the timing of the HTM is earlier (11-10 ka BP) on Ellesmere Island, based on elevation-corrected records of summer melt and water isotopes-at that same location our merged product suggests maximum HTM warmth to occur around 9.5 ka BP (Figure 2h). Recently, Lecavalier et al (2017) suggested that the timing of the HTM is earlier (11-10 ka BP) on Ellesmere Island, based on elevation-corrected records of summer melt and water isotopes-at that same location our merged product suggests maximum HTM warmth to occur around 9.5 ka BP (Figure 2h).…”
Section: Evaluating the Gis Surface Temperature Fieldssupporting
confidence: 52%
“…(b) TraCE-21Ka simulated AMOC strength (gray) and AMOC strength required to bring TraCE-21 K simulations and ice core reconstructions into agreement (orange). (h) Ellesmere Island temperature reconstruction (red curve) by Lecavalier et al (2017) and our merged product (gray curve) at that site. Horizontal bars denote data averages during the Last Glacial Maximum (22-18 ka BP) and "stable" part of the Holocene (10-0 ka BP).…”
Section: Temperature Seasonality Of Climate Forcingsmentioning
confidence: 99%
“…The resulting GrIS isostatic adjustment is therefore the combination of these local and non-local responses which make the GIA treatment rather complex. In principle, these nonlocal effects should be taken into account as they contribute to the sea-level variability, becoming especially relevant at the beginning of deglaciations when the ice mass loss is significantly induced by sea-level rise (Lecavalier et al, 2017). However, for the sake of simplicity, the GrIS isostatic adjustment is assumed here to be only due to local ice mass variations, as other works have done in the past (Greve and Blatter, 2009;Helsen et al, 2013;Huybrechts, 2002;Langebroek and Nisancioglu, 2016;Stone et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The retreat history of the GrIS during the last deglaciation was reconstructed using an ice sheet model constrained with evidence of past margin positions and relative sea-level indicators [103,112]. The reconstruction provides important constraints for model spin-up to the present day, when representing the correct loading history and isostatic response.…”
Section: Paleo Ice Sheet Simulationsmentioning
confidence: 99%